FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENDAMPING PASIEN BERSALIN DALAM MENJALANKAN PROTOKOL COVID 19 - Nina Fitri; Dewi Fanny (Universitas Fort de Kock Bukittinggi, 2021)
Non-natural disasters caused by Corona Virus or Covid-19 are the increasing number of victims and property losses, expanding the coverage of areas affected by disasters, and having implications for broad socio-economic aspects in Indonesia. The initial survey obtained from IV Koto Community Health Center from 10 maternal assistants during Covid 19 era, 4 people had high knowledge, 6 people had low knowledge, 19 people had negative attitudes and 4 people had positive attitudes about the Covid 19 protocol. The general purpose of this study was to determine Factors Related to Compliance of Maternity Patient Assistants in Implementing Covid 19 Protocol in the New Normal Era in IV Koto Community Health Center Working Area in 2021.It was analytical descriptive research uses a cross sectional design. The data were collected using primary data, parents and husbands of mothers who gave birth in IV Koto Working Area were chosen as the samples. They were 40 samples. They had been selected by using accidental sampling.From the research results, it was found that there was a significant relationship between beliefs p = 0.008 (p <0.05). knowledge p = 0.000 (p <0.05). attitude p = 0.027 (p <0.05). In short, it can be concluded that all variables had a relationship with the compliance of the patient's assistant with Covid 19 protocol in IV Koto Community Health Center. It is suggested to the health officers to motivate the community to obey the Covid 19 protocol.Keywords : Obedience, Belief, Knowledge, Attitude, Covid 19